2017
DOI: 10.1002/2016wr020335
|View full text |Cite
|
Sign up to set email alerts
|

A modeling approach to identify the effective forcing exerted by wind on a prealpine lake surrounded by a complex topography

Abstract: The representation of spatial wind distribution is recognized as a serious difficulty when modeling the hydrodynamics of lakes surrounded by a complex topography. To address this issue, we propose to force a 3‐D lake model with the wind field simulated by a high‐resolution atmospheric model, considering as a case study a 61 km2 prealpine lake surrounded by mountain ranges that reach 1800 m above the lake's surface, where a comprehensive data set was available in the stratified season. The improved distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…In oceanography, three-dimensional models have a long history of application (see e.g., [19]). They became more popular in limnological studies in the early 2000s [20][21][22]) and are now used frequently to understand physical (e.g., [23,24]) and biological (e.g., [25,26]) processes in lakes and to assess the effects of lake management on oxic conditions [27] or phytoplankton dynamics [28]. In shallow lakes, three-dimensional models are commonly applied to analyze the occurrence of anoxia [29], resuspension events [30], cyanobacteria blooms [31] and to support management, e.g., by identifying critical nutrient loads [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In oceanography, three-dimensional models have a long history of application (see e.g., [19]). They became more popular in limnological studies in the early 2000s [20][21][22]) and are now used frequently to understand physical (e.g., [23,24]) and biological (e.g., [25,26]) processes in lakes and to assess the effects of lake management on oxic conditions [27] or phytoplankton dynamics [28]. In shallow lakes, three-dimensional models are commonly applied to analyze the occurrence of anoxia [29], resuspension events [30], cyanobacteria blooms [31] and to support management, e.g., by identifying critical nutrient loads [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…For Lake Geneva, it has been reported that the wind in Pully may be weaker than the global wind over the lake (Lemmin and D'Adamo, 1997). The surrounding topography greatly influences the wind field over the lake and its impact on BSIWs (Valerio et al, 2017).…”
Section: Calibration Resultsmentioning
confidence: 99%
“…In situ measurements, laboratory experiments and theoretical considerations have shown that the response of a stratified basin to wind depends on the strength, duration and homogeneity of the wind field as well as the geometry of the basin and the stratification of the water column (Valerio et al, 2017;Valipour et al, 2015;Stevens and Imberger, 1996;Mortimer, 1974). The typical assumption consists in considering the stratified water body as a two-layer system with different densities and thicknesses.…”
Section: Hydrodynamics Of Vertical Mixing In Lakesmentioning
confidence: 99%
“…As a result, typical physically and conceptually based hydrological models are seldom employed to estimate daily inflow into such systems as flow records are often unavailable or insufficient to calibrate those models with desired certainty (Bárdossy, 2007;Devi, Ganasri, & Dwarakish, 2015). Consequently, estimation of daily inflows time series at ungauged catchments of large lakes remains one unsolved challenges in hydrology (Archfield & Vogel, 2010;Gibson, Birks, Jeffries, & Yi, 2017;Seibert & Beven, 2009;Valerio, Cantelli, Monti, & Leuzzi, 2017). Nevertheless, for refined and sustainable water management of large lakes and their catchments, there is an increasing demand for inflow information at catchments where no flow data are available.…”
mentioning
confidence: 99%